Promet s kmetijskimi zemljišči - Rejc, Žiga (Podjetje in delo, 2018)
The Agricultural Land Act (Zakon o kmetijskih zemljiščih, ZKZ) defines the holders of pre-emptive rights as well as special administrative procedure regulating legal transactions with agricultural land. The aim of the procedure is to ensure that legally privileged potential buyers can effectively claim their special rights in such transactions. Such pre-emptive rights are, however, only granted by law in order to help secure not only the continuity of agricultural production but also conservation of cultural and social communities in the countryside - thereby in the public interest. As such, they have to be exercised in conformity with the principle of proportionality. In this respect, the paper identifies some provisions of ZKZ that, on one hand, pose disproportionate limits to the principle of free trade, whereas on the other, the law also too widely defines the pre-emptive rights for some of the beneficiaries. All in all, such imperfections enable speculative trading with agricultural land that is not only contrary to the aims of ZKZ itself, but also, in some aspects, to the very principles of the EU law.
Keywords: kmetijska zemljišča; obid zakona; predkupna pravica; prodaja kmetijskih zemljišč; promet s kmetijskimi zemljišči; slamnati kupci; Zakon o kmetijskih zemljiščih; zloraba pravice